Effects of different precooling techniques on repeat sprint ability in team sport athletes - Brade, Carly; Dawson, B.; Wallman, K. (2014)
This study aimed to compare the simultaneous use of internal and external precooling methods with singular methods and their effect on repeated sprint cycling in hot/humid conditions. Twelve male team sport players completed four experimental conditions, initially involving a 30-min precooling period consisting of either a cooling jacket (J); ingestion of an ice slushy ice slushy; combination of cooling jacket and ice ingestion (J + ice slushy); or control (CONT). This was followed by 70 min of repeat sprint cycling (in~35°C, 60% relative humidity [RH]), consisting of 2×30-min halves, separated by a 10-min half-time period where the same cooling method was again used. Each half comprised 30×4 s maximal sprints on 60 s, interspersed with sub-maximal exercise at varying intensities. Total mean power and work performed were significantly higher (p = 0.02) in J + ice slushy (233.6±31.4 W) compared to ice slushy (211.8±34.5 kJ), while moderate effect sizes (ES: d = 0.67) suggested lower core temperatures (TC) in J + ice slushy (36.8±0.3°C) compared to J (37.0±0.3°C) and CONT (37.0±0.3°C) following precooling. A moderate ES (d = 0.57) also indicated lower TC in J + ice slushy (38.2±0.3) compared to ice slushy (38.4±0.4°C) after half-time cooling. Change (?) in mean skin temperature over half-time cooling was significantly greater (p = 0.036) for J (1.0±0.4°C) compared to ice slushy (0.5±0.5°C), and ES (d = 0.5-1.10) also suggested a greater ? for J compared to the other conditions. Sweat loss was significantly greater (p < 0.05) in ice slushy and J + ice slushy compared to J and CONT. In conclusion, a combination of (external and internal) body cooling techniques may enhance repeated sprint performance in the heat compared to individual cooling methods. © 2014 Copyright European College of Sport Science.